The Effect of Age and Duration of Fasting on Performance and Carcass Characteristics of Broiler Chicken - S. Banong; M. R. Hakim (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
The research was conducted to evaluate the effect of age and duration of fasting on performance and carcass characteristics of broiler chicken. One hundred and eight day old chick of broiler Cobb SR 707 were randomly assigned into floor pen (0.5 m x 1.0 m x 0.8 m), in which each pen was filled with four chicks. The experiment was performed in a factorial arrangement (3 x 3) according to completely randomised design with three replication for each treatment combination. The first factor was duration of fasting, i.e. 0 h (control), 2 h (12.00-14.00 p.m.), and 4 h (11.00 a.m to 15.00 p.m). The second factor was the age of chicks when fasting was introduced, i.e. 2, 3 and 4 weeks, respectively. The result of study indicated that fasting program up to 4 h daily begin at 2 weeks of age did not alter broiler performance. Similarly, carcass characteristics, especially carcass percentage, carcass cuts and abdominal fat were not affected by fasting program. Under the research condition, fasting program did not increase the farming efficiency of broiler chicken.